Ultrasonic roll bite measurements in cold rolling: Contact length and strip thickness. (February 2018) - Carretta, Yves; Hunter, Andrew; Boman, Romain; Ponthot, Jean-Philippe; Legrand, Nicolas; Laugier, Maxime; Dwyer-Joyce, Rob
In cold rolling of thin metal strip, contact conditions between the work rolls and the strip are of great importance: roll deformations and their effect on strip thickness variation may lead to strip flatness defects and thickness inhomogeneity. To control the process, online process measurements are usually carried out; such as the rolling load, forward slip and strip tensions at each stand. Shape defects of the strip are usually evaluated after the last stand of a rolling mill thanks to a flatness measuring roll. However, none of these measurements is made within the roll bite itself due to the harsh conditions taking place in that area. This paper presents a sensor capable of monitoring strip thickness variations as well as roll bite length in situ and in real time. The sensor emits ultrasonic pulses that reflect from the interface between the roll and the strip. Both the time-of-flight of the pulses and the reflection coefficient (the ratio of the amplitude of the reflected signal to that of the incident signal) are recorded. The sensor system was incorporated into a work roll and tested on a pilot rolling mill. Measurements were taken as steel strips were rolled under several lubrication conditions. Strip thickness variation and roll-bite length obtained from the experimental data agree well with numerical results computed with a cold rolling model in the mixed lubrication regime.